Effects of antacids and food on absorption of famotidine. - Lin, J H (1987)
The effect of a high potency antacid and food on the bioavailability of famotidine was studied in 17 healthy volunteers in an open randomized three-way cross-over trial. After an overnight fast, famotidine was administered to each subject as follows: 40 mg famotidine orally alone; 40 mg orally with antacid; and 40 mg orally with a standard breakfast. Coadministration of the antacid caused a small but significant reduction in the maximum plasma concentration (Cmax) of famotidine from 81.1 +/- 54.2 to 60.8 +/- 21.6 ng ml-1 (P less than 0.05) and a small decrease in the area under plasma concentration-time curve [AUC] from 443.3 +/- 249.2 to 355.0 +/- 125.1 ng ml-1 h (P greater than 0.05). However, there was only a minimal effect of food on these parameters; the Cmax and [AUC] were 81.6 +/- 29.6 ng ml-1 and 434.8 +/- 145.9 ng ml-1 h, respectively.